30 Years to the AIC. A Speech at Beit Sahur - Shimshon Bichler (The Bichler and Nitzan Archives, 2013)
The following is the text of a presentation delivered by Dr. Shimshon Bichler at the 30-year celebration of the Alternative Information Center (AIC), on October 5, 2013. Dr. Bichler is a political economist and veteran member of the AIC Board of Directors.
Keywords: P; P1; 330; conflict; Israel; Palestine